If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x=-3(3x-4)
We move all terms to the left:
6x-(-3(3x-4))=0
We calculate terms in parentheses: -(-3(3x-4)), so:We get rid of parentheses
-3(3x-4)
We multiply parentheses
-9x+12
Back to the equation:
-(-9x+12)
6x+9x-12=0
We add all the numbers together, and all the variables
15x-12=0
We move all terms containing x to the left, all other terms to the right
15x=12
x=12/15
x=4/5
| x=855*0.16*3.25 | | -2x-11=-32 | | X^2=-4+100x | | (27/8)^(9/4)=(9/4)^x | | X^2=4+100x | | 3x2–6x+12=0 | | 15=-34y | | 16=5x-17 | | 3x-2/10=0 | | 8x+54=180 | | 18=3y+ | | 6b =2 | | 180=50+4-8x | | 8+3(1-4n)=-7n-(6n-1) | | 8x-4+50=180 | | -2(1-2r)-(3r+1)=-3 | | x/3(x-5)=x+21 | | 2x-17+2x-18=13 | | 12(2w-5)=84 | | 2(3+r)-3(r+2)=2 | | 55=3(1+3v)+4v | | (0,75x-6)+3=8 | | 5x–4=3x=6 | | 4(r+3)=32 | | (4*3)^x+3^x=15 | | w+15=-29 | | X/4+6=12,x | | c-21=16 | | -120x=-6 | | 2y+15=45+y | | 20x=1,3 | | -4=4-2r-2r |